Architectural Effects of Star‐Shaped "Structurally Nanoengineered Antimicrobial Peptide Polymers" (SNAPPs) on Their Biological Activity. Issue 21 (2nd September 2018) - Shirbin, Steven J.; Insua, Ignacio; Holden, James A.; Lenzo, Jason C.; Reynolds, Eric C.; O'Brien‐Simpson, Neil M.; Qiao, Greg G.
Abstract: In this work, the effect of two key structural parameters, number of arms and arm length, of star‐shaped "structurally nanoengineered antimicrobial peptide polymers" (SNAPPs) on their antimicrobial activity and biocompatibility, is investigated. A library of star‐shaped SNAPPs is prepared, containing varying arm numbers and arm lengths. Antimicrobial assays are then performed to assess the capacity of the SNAPPs to disrupt the membrane, inhibit the growth, and kill pathogenic bacteria. A major finding of the study is that increasing arm number and length of SNAPPs enhanced antimicrobial activity, which can be respectively attributed to the higher local concentrations of polypeptide arms and increased α‐helical content. SNAPP architecture is shown to affect the bacteria membrane state and therefore mechanism of killing. Two more potent structures with up to twice the antimicrobial activity of the previously reported SNAPP are discovered in this process. Toxicities of the SNAPPs also increase with arm number and arm length, however therapeutic index calculations identified a 16‐arm SNAPP and an easier to prepare 4‐arm SNAPP as the best therapeutic agents. The biocompatibility of the SNAPP with the best biological activity is also evaluated in vivo, showing no markers of systemic damage in mice. Abstract : The effect of two key architectural parameters of star‐shaped 'structurally nanoengineered antimicrobial peptide polymers' (SNAPPs) on their biological activity, is examined. It is found that SNAPPs bearing more and longer polypeptide arms display stronger antimicrobial effects, leading to the discovery of two more potent SNAPPs and new architectures which are easier to synthesize without losing significant biological activity.